Protecting investors in equity crowdfunding: An empirical analysis of the small investor protection act - Maximilian Goethner; Lars Hornuf; Tobias Regner (Friedrich Schiller University Jena, 2020)
During the past decade, equity crowdfunding (ECF) has emerged as an alternative funding channel for startup firms. In Germany, the Small Investor Protection Act became binding in July 2015, with the legislative goal to protect investors engaging in this new asset class. Since then, investors pledging more than 1,000 EUR now must self-report their income and wealth. Investing more than 10,000 EUR in a single ECF issuer is only possible through a corporate entity. We examine how the Small Investor Protection Act has affected investor behavior at Companisto, Germany's largest ECF portal for startup firms. The results show that after the new law became binding, sophisticated investors invest less on average while casual investors invest more. Moreover, the signaling capacity of large investments has disappeared.
Keywords: E22; G18; G38; K22; L26; 330; Equity crowdfunding; Crowdinvesting; Investor protection